How is the CGIAR Approaching Climate Change Issues? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Roberto Quiroz from CIP (International Potato Centre). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya